Development of Physical Qualities through Training in Volleyball Players (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article extensively covers the productive use of qualities such as speed, agility, strength, agility, flexibility in the training plan of volleyball players. In training processes, it requires athletes to have the maximum level of agility, jumpiness, elegance, quick-thinking, able to quickly understand and "useful" response to the situation on the field in peak conditions. The article is intended for mentoring coaches and those involved in this type of volleyball sport.